HISTÓRIA DEMOGRÁFICA DO SARS-COV-2 NO ESTADODO ESPÍRITO SANTO, BRASIL, BASEADA EM UMA ABORDAGEM FILOGEOGRÁFICA - Vargas, Aura Marcela Corredor (2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the 2019 coronavirus disease outbreak (COVID-19), currently remains a public health event, of which on March 11, 2020, the WHO (World Health Organization) declared a pandemic. In light of this, the disease has spread to all continents, causing more than 627 million infections worldwide, and more than 6.5 million of deaths (more than 687 thousand in Brazil). The first case of COVID-19 in the state of Espírito Santo (ES) was on February 29, 2020, and currently the state of ES registers more than 1.2 million contagions. The rapid spread of SARS-CoV-2 has led to the appearance of new lineages, making phylogeography as a necessary approach to understand the dynamics and evolution of the virus, through genetic sequences deposited in the GISAID database. This research represents the first study with a phylogeographic approach of SARS-CoV-2, aiming to study the demographic and genetic history of SARS-CoV-2 in the state of ES, from genomic sequences obtained between February 29, 2020 and January 18, 2022. To fulfill this purpose, 317 genetic sequences of SARS-CoV-2 from the state of ES were recopied in order to identify SARS-CoV-2 lineages in the state of ES, their haplotypes, infer a network, characterize the genetic diversity and structure in the subpopulations that make up the state of ES, and finally reconstruct the population demography of the virus. The findings indicated that during the established period there was a high diversity of lineages, 22 in total. The most frequent lineage detected in the state of ES was AY.99.2 (32.49%), and by joining the lineages comprising the Delta variant, it was found to be the only variant detected in all subpopulations of the state. The Metropolitan subpopulation of Vitoria had the highest number of lineages (14) compared to the other subpopulations of the state. Also, it showed a high haplotypic diversity value (h=0.9994), and a low nucleotide diversity (π=0.00134), which demonstrates a recent population expansion, supported in the network by the high number of unique haplotypes. Furthermore, the discrete differentiation between the state subpopulations is evidenced in the network by the few shared haplotypes. Finally, the spatio-temporal analysis of the SARS-CoV-2 population demonstrated a hypothesized oscillation in the expansion of Ne in the two- year period, which correlated to the epidemiological waves happened int the state. As a main contribution, this study presents an analysis of the historical, demographic and genetic events of SARS-CoV-2 in the state of ES, using a phylogeographic approach to understand the evolution of the virus in the context of the COVID-19 pandemic at state, national, global levels, in addition to the advancement in viral phylogeographic studies.